A study of stakeholder group's preferences for progressive public administration or new public management in public sector accountancy - Vivian, Bruce (My University, 2016)
The success of public sector accountancy reform as part of the ‘new public management’ is dependent on the common goals of all stakeholders. This research applies new institutionalism to understand the isomorphic pressures being exerted by accounting professionals and international organisations on government agencies to drive these reforms. It analyses the preferences of different stakeholder groups to the opposing doctrines of new public management and progressive public administration. These preferences were analysed through a content analysis of the comments letters submitted to the IPSASB during their recent conceptual framework project. Accounting professionals were found to be motivated by normative and mimetic isomorphism to bring about institutional change under the themes of private sector mimicry, inter-generational equity and performance focused reporting. They were strongly motivated to lobby for these changes by their own self-interest. Government agencies showed a resistance to these changes. Their self-interest reduced the level to which they were influenced by isomorphic pressures. Such resistance was strongest in Canada but weakest in Australia and the United Kingdom. No conclusions could be reached on the role of international organisations in supporting institutional change.
A research report submitted In partial fulfilment of the requirements for the degree of Master of Commerce (Accounting), University of the Witwatersrand
Keywords: Finance, Public--Accounting